The Shame–Blame Game: Is It Still Necessary? A National Survey of Shame-based Teaching Practice in Canadian Plastic Surgery Programs - Kaitlin S. Boehm, MD; Connor McGuire, MHSc; Colton Boudreau, MSc; Danielle Jenkins, BScN; Osama A. Samargandi, MD, MHSc; Sarah Al-Youha, MD, PhD, FRCSC; David Tang, MD, FRCSC (Plastic and Reconstructive Surgery, Global Open, 2019)
Background:. As understanding of poor physician mental health and burnout strengthens, it is becoming important to identify factors that detract from wellbeing. Shame-based learning (SBL) is detrimental to psychological health and can contribute to burnout, substance abuse and suicide. This study endeavoured to quantify the unknown prevalence and effects of SBL in Canadian plastic surgery programs. Methods:. An electronic survey was sent to all attending surgeons and trainee (residents and fellows) members of the Canadian Society of Plastic Surgeons. SBL was assessed using a validated questionnaire. Data was analyzed using descriptive statistics and thematic analysis. Results:. 98 responses (14.7%) comprising of 63 attending surgeons and 36 trainees were received. The majority of attending surgeons (78 percent) and trainees (67%) have been shamed. Fourteen percent of trainees and 9% of attending surgeons felt that SBL is necessary. The most common event provoking shaming for trainees was wrong answers (56%) and for attending surgeons was disagreement in clinical care (21%). For both groups, shamers were in positions of authority. The most common effect of SBL in trainees was a loss of self-confidence (53%), compared to no negative effect in attending surgeons (49 percent). Thirty-nine percent of trainees dealt with shaming events with support from fellow trainees (39 percent), while attending surgeons kept it to themselves (40 percent). Conclusion:. SBL is present in Canadian plastic surgery residency programs and has numerous detrimental effects. To foster better mental health, residency programs should identify ongoing SBL and make efforts to transition to healthier feedback strategies.